Krebs von den Lungen-6 (KL-6) and Surfactant-D as Biomarkers of Interstitial Lung Disease: A Literature Review - Fachrucha, Fanny; Fadhillah, Muhamad Rizqy; Aflah, Syazatul Syakirin Sirol (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Interstitial Lung Disease (ILD) is a group of lung diseases characterized by various patterns of lung tissue damage, including inflammation and fibrosis of the lung interstitium, both with known or unknown causes (idiopathic). In establishing the diagnosis of ILD, a comprehensive approach including history-taking, physical examination, and supporting examinations, is needed and managed in a multidisciplinary manner. Biomarkers are diagnostic tools known to be accessible, inexpensive, reproducible, and non-invasive for helping diagnose ILD patients. Growing evidence has supported the idea that many biomarker molecules can detect lung injury in ILD, including Krebs von de lungen-6 (KL-6) and Surfactant D (SP-D). KL-6 and SP-D could be utilized in the detection, disease monitoring, prognostication, and therapeutic responses of ILD patients. This review aimed to discuss several potential Kl-6 and SP-D biomarkers against ILD and discusses their clinical utility.